If f(c)=0, which of the following statements must be true?
___________________________________________
○A. The point (-c, 0) lies on the graph of f(x)

○B. The point (0, c) lies on the graph of f(x)

○C. x-c is a factor of f(x)

○D. x+c divides evenly into f(x)​

Answers

Answer 1

Answer:

C.

Step-by-step explanation:

If f(c)=0 then (c,0) is on the graph.

In general, if f(a)=b then (a,b) is on the graph.

By factor theorem if f(c)=0 then x-c is a factor.

If x-c is a factor then x-c will divide f(x) evenly.  We know this because the remainder will be 0 because we know x-c is a factor of f.

The only choice that I have said in this whole thing that is true is C.

Answer 2

Answer:  The correct option is

(C) x-c is a factor of f(x).

Step-by-step explanation:  Given that for a function f(x), f(c) = 0.

We are to select the true statement from the given options.

We have the factor theorem as follows :

Factor theorem :  If p(a) = 0 for a polynomial function p(x), then (x-a) is a factor of p(x).

According to the given information, we have

f(c) = 0.

Therefore, (x-c) is a factor of f(x).

Thus, (C) is the correct option.


Related Questions

What is the value of y?
Y + 30°
A. 85°
B. 55
c. 110°
D. 10°​

Answers

Answer:

B. 55°

Step-by-step explanation:

Note that the total angle measurements of a triangle is = 180°.

Add all the measurements together:

40 + y + 30 + y = 180

Simplify. Combine like terms:

(40 + 30) + (y + y) = 180

70 + 2y = 180

Isolate the y. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS. First subtract, then divide.

Subtract 70 from both sides:

70 (-70) + 2y = 180 (-70)

2y = 180 - 70

2y = 110

Divide 2 from both sides:

(2y)/2 = (110)/2

y = 110/2

y = 55

B. 55° is your answer.

~

Answer: The answer is B, 55 degrees.

Step-by-step explanation:

You substitute 55 into y, making it 55+85, +55, +40, making it 180 degrees. Since all sides in a triangle add up to 180, B is your correct answer.

Hope that helps!

If N || P and P bisects M then _____ (13)

Answers

If N || P and P bisects M then, line N must be perpendicular to line M (N ⊥ M) (option A).

How to determine the relationship between line N and line P?

From the given diagram we are told that line N is parallel to line P and line P is perpendicular to line M.

So line P bisect line M and it is also perpendicular to line M, we can deduce the following;

line N is perpendicular to line M

So based on the information given to us, we can only deduce the relationship between M, N and P.

Hence N must be parallel to P, then line P must be perpendicualr to line M and line N and line M must be perpendicular to each other.

help!!!!!!!!!!! If one factor of x2 + 2x – 24 is (x+6), what is the other factor?

(x+8)
(x–8)
(x+4)
(x−4)

Answers

Answer:

the other factor is (X-4)

Step-by-step explanation:

this is a perfect square trinomial so the two factors should interact the next way:

x2 + 2x – 24

(X+6) * (X-4)     the two numbers added give you the middle       .                                 .                        number  (2)

                       

                        and multiplied give you the final number (24)  so:

1)     +6-4 =  2

and

2)     +6 * - 4  =  -24

x^2 + 2x -24

So I know one factor is gonna be 6. I have to find a number that multiply with 6 is equal -24. But when 6 add that number the answer must equal 2.

So as you can see 6 multiply -4 is -24. 6+ (-4) is 2z

The answer is D. (X-4)

Hope this helps!

You brought 9 feet of elastic to make hair ties each hair ties need 3 3/8 inches of elastic how many hair ties can you make

Answers

Answer:

[tex]32\ hair\ ties[/tex]

Step-by-step explanation:

we know that

To make one hair ties is needed 3 3/8 inches of elastic

so

using proportion

Find out how many hair ties can you make with 9 feet of elastic

Remember that

[tex]1\ ft=12\ in[/tex]

Convert 9 ft to inches

[tex]9\ ft=9*12=108\ in[/tex]

Convert mixed number to an improper fraction

[tex]3\frac{3}{8}\ in=\frac{3*8+3}{8}=\frac{27}{8}\ in[/tex]

using proportion

[tex]\frac{1}{(27/8)}=\frac{x}{108}\\\\x=108*8/27\\\\x=32\ hair\ ties[/tex]

Nick is solving the equation 3x2=20−7x with the quadratic formula.

Which values could he use for a, b, and c?



a = 3, b = ​−7​ , c = 20

a = 3, b = 7, c = −20

a = 3, b = ​−20​ , c = 7

a = 3, b = 20, c = −7

Answers

Answer: Second option.

Step-by-step explanation:

Given a Quadratic equation in the form:

[tex]ax^2+bx+c=0[/tex]

It can be solve with the Quadratic formula. This is:

[tex]x=\frac{-b\±\sqrt{b^2-4ac} }{2a}[/tex]

In this case, given the Quadratic equation:

[tex]3x^2=20-7x[/tex]

You can rewrite it in the form [tex]ax^2+bx+c=0[/tex]:

- Subtract 20 from both sides of the equation:

[tex]3x^2-20=20-7x-20\\\\3x^2-20=-7x[/tex]

- Add [tex]7x[/tex] to both sides of the equation:

[tex]3x^2-20+7x=-7x+7x\\\\3x^2+7x-20=0[/tex]

Therefore, you can identify that:

[tex]a=3\\b=7\\c=-20[/tex]

Answer:

option B. a=3, b=7, c=-20

I just took the test :)

Step-by-step explanation:

Ellie wants to change her password which is ELLIE9 but with same letters and number. In how
many ways she can do that?
P = 256
P = 150
P = 200
P = 179

Answers

[tex]\dfrac{6!}{2!2!}-1=\dfrac{3\cdot4\cdot5\cdot6}{2}-1=180-1=179[/tex]

The number of passwords she can create is an illustration of permutations.

The number of ways to create the password is 179

The password is given as: ELLIE9

The number of characters in the password is:

[tex]n = 6[/tex]

L and E are repeated twice.

So, we have

[tex]L = 2[/tex]

[tex]E = 2[/tex]

The number of new passwords to create is then calculated as:

[tex]Passwords = \frac{n!}{L!E!} - 1[/tex] --- 1 represents the current password

This gives

[tex]Passwords = \frac{6!}{2!2!} - 1[/tex]

Expand

[tex]Passwords = \frac{6 \times 5 \times 4 \times 3 \times 2!}{2! \times 2 \times 1} - 1[/tex]

[tex]Passwords = \frac{6 \times 5 \times 4 \times 3 }{2 \times 1} - 1[/tex]

Simplify

[tex]Passwords = 180 - 1[/tex]

Subtract

[tex]Passwords = 179[/tex]

Hence, the number of ways to create the password is 179

Read more about permutations at:

https://brainly.com/question/1216161

Find the midpoint of the segment between the points (15,−9) and (−2,−18)

Answers

Answer:

(13/2,   -27/2)

Step-by-step explanation:

The midpoint is found by using

midpoint = (x1+x2)/2,  (y1+y2)/2

               = (15+-2)/2,  (-9+-18)/2

                 =13/2,   -27/2

Explain the effect of c on the graph of y=f(x) for the function y=f(x)+c ?

Answers

Answer:

Shifts it up c units.

Step-by-step explanation:

The '+ c'  will move the whole graph upwards c units.

By translation of axis, the effect of c on the graph of y=f(x) for the function y=f(x)+c is it shifts up the curve by c units.

What is the effect of c on the graph of y=f(x) for the function y=f(x)+c ?

The translation of axis on any curve y = f(x) is the shifting of the graph by a definite unit from the original equation or curve.

If the curve is given as y = f(x) ± a, then for +a , it shifts the curve on the graph upwards on y axis by a units and for -a, it shifts the curve on the graph downwards on y axis by a units.

The given function is y = f(x) and thus for the graph y = f(x) + c, from the principle of translation of axis, it shifts the curve upwards on y-axis by c units.

Therefore, by translation of axis, the effect of c on the graph of y=f(x) for the function y=f(x)+c is it shifts up the curve by c units.

To learn more about translation of axis, refer -

https://brainly.com/question/13636820

#SPJ2

What is the completely factored form of 2x^3+4x^2-x

Answers

Answer:

I think it's:

x(2x^2+4x-1)

What is the x-intercept of the line shown below? Enter your
answer as a coordinate pair.

Answers

Answer:

(0,3)

Step-by-step explanation:

The x-intercept is the point in the graph where x=0.  On the graph you can see that when x=0, y=3.  Therefore our coordinate is (0,3)

Our coordinate pair in the graph is (0,3)

The x-intercept of a line occurs where the line intersects the x-axis, meaning the y-coordinate is zero. In the provided graph, when x equals zero, the corresponding y-value is three. Thus, the coordinate pair (0,3) represents the point where the line intersects the x-axis. This result indicates that when x equals zero, the line crosses the y-axis at a height of three units.

To find the x-intercept, one sets y equal to zero and solves for x. In this case, when y equals zero, there is no such point on the line, so the x-intercept does not exist. Therefore, the coordinate (0,3) accurately identifies the x-intercept of the given line, demonstrating the point where it intersects the x-axis on the graph.

Which is the end point of a ray

Answers

Answer:

Point S is the endpoint of a ray.

Step-by-step explanation:

A ray is a line with a single endpoint (or point of origin) that extends infinitely in one direction. Point S is the endpoint for rays SR, SU, and ST.

The ray's endpoint is Point S.

Given is a figure of an angle S being divided into two angles by the ray SU,

We need to find the endpoint of the ray,

So,

A ray's endpoint is the singular location where the ray comes to an end.

A ray is a line that emanates from an initial point known as the endpoint or origin and travels endlessly in one direction.

A ray, as opposed to a line segment, has no set length and travels in one direction indefinitely.

A ray's terminus, which is also its beginning point, is typically identified as a single point in space.

A ray is a line that has a single terminus (or point of origin) and travels in a single direction indefinitely.

The intersection of rays SR, SU, and ST is at point S.

Hence the ray's endpoint is Point S.

Learn more about ray of a line click;

https://brainly.com/question/13144568

#SPJ6

Solve for f(-1).

F(x) = -3x + 3
F(-1) =

Answers

F(x) = -3x + 3  

replace x in the equation with -1:

F(-1) = -3(-1) + 3

Simplify:

f(-1) = 3+3

f(-1) = 6

What is the simplest form of the expression (–12.7y – 3.1x) + 5.9y – (4.2y + x)?

Answers

Answer:

-11y - 4.1x

Step-by-step explanation:

[tex](-12.7y-3.1x)+5.9y-(4.2y+x)\\\\=-12.7y-3.1x+5.9y-4.2y-x\qquad\text{combine like terms}\\\\=(-12.7y+5.9y-4.2y)+(-3.1x-x)\\\\=-11y-4.1x[/tex]

The simplest form of given expression is  [tex]-11y-4.1x[/tex].

What is an expression?

Expressions in math are mathematical statements that have a minimum of two terms containing numbers or variables, or both, connected by an operator in between.

Given expression

[tex](-12.7y-3.1x)+5.9y-(4.2y+x)[/tex]

= [tex]-12.7y-3.1x+5.9y-4.2y-x[/tex]

Combine like terms

= [tex](-12.7y+5.9y-4.2y)+(-3.1x-x)[/tex]

= [tex]-11y-4.1x[/tex]

The simplest form of given expression is  [tex]-11y-4.1x[/tex].

Find out more information about expression here

https://brainly.com/question/14083225

#SPJ2

a brokerage firm charges 1 1/4% if its fee on stock purchase was 400$ what was amount of purchase?​

Answers

let's say the amount purchased was "x", so then that's the 100%.

if we know that 400 is the 1¼% and "x" is the 100%, what is "x"?

[tex]\bf \begin{array}{ccll} amount&\%\\ \cline{1-2} x&100\\ 400&1\frac{1}{4} \end{array}\implies \cfrac{x}{400}=\cfrac{100}{1\frac{1}{4}}\implies \cfrac{x}{400}=\cfrac{100}{\frac{1\cdot 4+1}{4}}\implies \cfrac{x}{400}=\cfrac{\frac{100}{1}}{\frac{5}{4}} \\\\\\ \cfrac{x}{400}=\cfrac{\stackrel{20}{~~\begin{matrix} 100 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}{1}\cdot \cfrac{4}{~~\begin{matrix} 5 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies \cfrac{x}{400}=80\implies x=32000[/tex]

8. Which expression is equivalent
to 24 + 15?
A 2 X (12 + 7)
B 3 X (8 + 5)
C 5 x (8 + 3)
D 8 X (3 + 7)

Answers

B
This is an expand the brackets question. So you multiply the number on the outside of the bracket by the numbers on the inside of the bracket.
3*8=24
3*5=15

Answer:

B

Step-by-step explanation:

Given

24 + 15 ← factor out 3 from each term

= 3(8 + 5)

As a check

24 + 15 = 39 and

3(8 + 5) = 3 × 13 = 39

Hence 24 + 15 = 3(8 + 5) → B

What is the value of -4 squared +(5-2)(-6)

-------

I need help ASAP!!!

Answers

-4^2= 16

anytime you have a negative number squared it results in the positive version

ex. -4×-4 equals -16, except it should be positive instead of negative.

now 16+-10×-6

-10×-6=60

16+60=76

Please vote my answer brainliest. thanks!

A distance of 150 km was covered by a motorcyclist traveling at an average speed of 75 km/h, by a bus at 60 km/h, a truck at 50 km/h, and a bicyclist at 20 km/h. How much time did each require to travel the entire distance? Explain why speed and the time needed to travel 150 km are inversely proportional quantities?

I need to know how to explain the last sentence.

Answers

Answer:

Motorcyclist: 2 hours

Bus: 2.5 hours

Truck: 3 hours

Bicyclist: 7.5 hours

Step-by-step explanation:

On a triangle, the vector from one vertex to another vertex is 〈-12,5〉. What is the length of the side?

Answers

Answer:

13

Step-by-step explanation:

The magnitude of a vector < a, b > is

[tex]\sqrt{a^2+b^2}[/tex]

Given < - 12, 5 > then the length of the side is

[tex]\sqrt{(-12)^2+5^2}[/tex]

= [tex]\sqrt{144+25}[/tex]

= [tex]\sqrt{169}[/tex] = 13

Final answer:

The length of the triangle side represented by the vector 〈-12,5〉 is calculated using the Pythagorean theorem and is found to be 13 units.

Explanation:

The student has asked about finding the length of the side of a triangle given a vector from one vertex to another. The vector given is 〈-12,5〉. The length of this side can be calculated using the Pythagorean Theorem for the magnitude of a vector, which states that the magnitude is the square root of the sum of the squares of the vector's components. The formula for the magnitude (or length) of a vector 〉 a, b 〉 is √(a² + b²).

For the vector 〈-12,5〉, the calculation would be:

a = -12b = 5Magnitude = √((-12)² + (5)²)

Which simplifies to:

√(144 + 25)√169Magnitude = 13

Therefore, the length of the side of the triangle is 13 units.

A new sweater costs $15.99. If the sweater is on sale for 1/4 off
its price, about how much
would you save?​

Answers

the sweater costs $15.99 regularly, however today is on sale, 1/4 off the regular price, how much is 1/4 of 15.99? well just their product, 15.99 * (1/4) = 3.9975.

that means that just for today, the sweater costs 15.99 - 3.9975.

so, today you're not really paying $15.99 for the sweater, you're paying 3.9975 less, so you're saving 3.9975.  That's $3.9975 that you won't be spending on it, thus saving it.

Answer:

4 dollars off

Step-by-step explanation:

The cost of the sweater is 15.99

You get 1/4 off

Multiply the cost by the discount

15.99 * 1/4

The questions asks about how much so you can round 15.99 to 16

16*1/4 = 4

You will get about 4 dollars off

how do you find the vertex of this equation: y = 6x-x2​

Answers

Answer:

(3,9)

Step-by-step explanation:

This is a quadratic equation.

A quadratic in standard form is [tex]y=ax^2+bx+c[/tex].

If we compare [tex]y=ax^2+bx+c[/tex] to [tex]y=6x-x^2[/tex], we see there [tex]c=0,b=6,a=-1[/tex].

Now to find the vertex, we first find the x-coordinate of the vertex which is:

[tex]\frac{-b}{2a}[/tex].

So now plug in our values:

[tex]\frac{-6}{2(-1)}=\frac{-6}{-2}=3[/tex]

So the corresponding y-coordinate can be found by the equation that relates x to y:  [tex]y=6x-x^2[/tex].

So we are plugging in 3 where we see x:  [tex]y=6(3)-3^2=18-9=9[/tex].

So the vertex is (3,9).

find the missing side, round to the nearest tenth place

Answers

Answer:

8.87

Step-by-step explanation:

The square means "right angle"

[tex] \sin(\alpha ) = \frac{x}{13} \\ \\ \sin(43) = \frac{ x }{13} \\ \\ x = \sin(43) \times 13 \\ x = 8.86597868081 \\ x = 8.87[/tex]

Derive the equation of the parabola with a focus at (-2,4) and a directrix of y=6 . Put the equation in standard form

Answers

Answer:

[tex]y = - \frac{1}{4} {(x + 2)}^{2} + 5[/tex]

Step-by-step explanation:

The vertex of this parabola is the midpoint of the focus (-2,4) and where the directrix intersects the axis of symmetry of the parabola (-2,6)

This parabola must open downwards due to the position of the directrix and has equation of the form:

[tex] {(x - h)}^{2} = - 4p(y - k)[/tex]

where (h,k) is the vertex.

This implies that:

[tex]h = - 2[/tex]

and

[tex]k = \frac{4 + 6}{2} = 5[/tex]

The value of p is the distance from the vertex to the focus:

[tex]p = |6 - 5| = 1[/tex]

We substitute all the values into the formula to get:

[tex](x - - 2)^{2} = - 4(1){(y - 5)}[/tex]

[tex] {(x + 2)}^{2} = - 4(y - 5)[/tex]

Or

[tex]y = - \frac{1}{4} {(x - 5)}^{2} + 5[/tex]

What is h(10) equal to? h:k→k^2-k
h(10)=[1]

Answers

[tex]h(k)=k^2-k\\\\h(10)=(10)^2-10=90[/tex]

What is the solution to the equation
1/4x+2=-5/8x-5

Answers

Answer: x = -8

Step-by-step explanation:

First you change 1/4 to 2/8. Then you want to get all of your x values on one side. So, +5/8x to each side turning your equation into 7/8x+2= -5. Then -2 from each side. 7/8x= -7. Finally get your variable by itself. Divide each side by 7/8 or multiple each side by its reciprocal (8/7)  

Solve the equation by graphing. If exact roots cannot be found, state the consecutive integers between which the roots are located. x2 +6x +8 = 0

Answers

Answer:

Step-by-step explanation:

The roots are very clear on the graph. I have left them unlabeled so that you can put the two points in.

The points are (-4,0) and (-2,0)

The graph was done on desmos which you can look up. The box in the upper left corner was filled with

y = x^2 + 6x + 8

HELPPPPPPPPPPP?????????

Answers

Answer:

14.21 units

Step-by-step explanation:

We can use distance formula to solve this easily.

Distance Formula is  [tex]D=\sqrt{(y_2-y_1)^2+(x_2-x_1)^2}[/tex]

Where

D is the distance

x_1, y_1 is the first points, respectively (let it be -6,-6)

x_2,y_2 is the second pints, respectively (let it be 3,5)

Substituting the values into the formula, we can get the value of D:

[tex]D=\sqrt{(y_2-y_1)^2+(x_2-x_1)^2}\\D=\sqrt{(5--6)^2+(3--6)^2}\\D=\sqrt{11^2+9^2}\\ D=\sqrt{202} \\D=14.21[/tex]

This is the distance, the first answer choice is right.

Solve by completing the square. x2+6x−6=0

Answers

For this case we must solve the following equation by completing squares:

[tex]x ^ 2 + 6x-6 = 0[/tex]

We add 6 to both sides of the equation:

[tex]x ^ 2 + 6x = 6[/tex]

We divide the middle term by 2, and square it:

[tex](\frac {6} {2}) ^ 2[/tex]

And we add it to both sides of the equation:

[tex]x ^ 2 + 6x + (\frac {6} {2}) ^ 2 = 6 + (\frac {6} {2}) ^ 2\\x ^ 2 + 6x + (3) ^ 2 = 6 + 9[/tex]

We rewrite the left part of the equation:

[tex](x + 3) ^ 2 = 15[/tex]

We apply root to both sides:

[tex]x + 3 = \pm \sqrt {15}[/tex]

We have two solutions:

[tex]x_ {1} = \sqrt {15} -3\\x_ {2} = - \sqrt {15} -3[/tex]

Answer:

[tex]x_ {1} = \sqrt {15} -3\\x_ {2} = - \sqrt {15} -3[/tex]

Answer:

[tex]x=-3\±\sqrt{15}[/tex]

Step-by-step explanation:

We have the following equation

[tex]x^2+6x-6=0[/tex]

To use the method of completing squares you must take the coefficient of x and divide it by 2 and square the result.

[tex](\frac{6}{2})^2=9[/tex]

Now add 9 on both sides of equality

[tex](x^2+6x+ 9)-6=9[/tex]

Factor the term in parentheses

[tex](x+3)^2-6=9[/tex]

Add 6 on both sides of the equation

[tex](x+3)^2-6+6=9+6[/tex]

[tex](x+3)^2=15[/tex]

Take square root on both sides of the equation

[tex]\sqrt{(x+3)^2}=\±\sqrt{15}[/tex]

[tex]x+3=\±\sqrt{15}[/tex]

Subtract 3 from both sides of the equation.

[tex]x+3-3=-3\±\sqrt{15}[/tex]

[tex]x=-3\±\sqrt{15}[/tex]

What is sqrt12x^8/sqrt3x^2 in simplest form

Answers

[tex]\bf \cfrac{\sqrt{12x^8}}{\sqrt{3x^2}}~~ \begin{cases} 12=&2\cdot 2\cdot 3\\ &2^2\cdot 3\\ x^8=&x^{4\cdot 2}\\ &(x^4)^2 \end{cases}\implies \cfrac{\sqrt{2^2\cdot 3(x^4)^2}}{\sqrt{3x^2}}\implies \cfrac{2\stackrel{x^2}{~~\begin{matrix} x^4 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~} ~~\begin{matrix} \sqrt{3} \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{~~\begin{matrix} x^2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~ ~~\begin{matrix} \sqrt{3} \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies 2x^2[/tex]

Answer:

2x^3 (C on edge)

Step-by-step explanation:

1200 people visited a museum. 240 of the visitors were children. what percent of the visitors were children?​

Answers

Answer:

20 percent

Step-by-step explanation:

To find the percentage that were children, we take the number of children over the total and multiply by 100%

There are 240 children and 1200 total people

240/1200 * 100%

.2*100%

20%

Answer:

20 Percent.

Step-by-step explanation:

240:1200*100 =

(240*100):1200 =

24000:1200 = 20

Find the following when : a=-2,b=3c=-1/3 7b-2/-a+1

Answers

Answer:  [tex]\bold{\dfrac{19}{3}}[/tex]

Step-by-step explanation:

[tex]\dfrac{7b-2}{-a+1}\\\\\\=\dfrac{7(3)-2}{-(-2)+1}\\\\\\=\dfrac{21-2}{2+1}\\\\\\=\dfrac{19}{3}[/tex]

Other Questions
Determine whether or not the vector field is conservative. If it is, find a function f such that F = f. If the vector field is not conservative, enter NONE. F(x, y, z) = 5y2z3 i + 10xyz3 j + 15xy2z2 k f(x, y, z) = + K For a brass alloy, the stress at which plastic deformation begins is 345 MPa (50,000 psi), and the modulus of elasticity is 103 GPa (15.0 106 psi). (a) What is the maximum load that may be applied to a specimen with a cross-sectional area of 130 mm2 (0.2 in2 ) without plastic deformation? (b) If the original specimen length is 76 mm (3.0 in.), what is the maximum length to which it can be stretched without causing plastic deformation? Llene el espacio en blanco con la mejor opcin. Este texto aparece en un tabln de anuncios: "____ voluntarios para trabajar en Ecuador este verano.A. Se solicitaban B. Se solicitanC. Se solicitD. Se solicita solve the inequality x +1 > 18 Write down the complete procedure for creating ExcelSheet. Erik observes that when he dresses in business casual, people seem more comfortable approaching him. He wants to know if this is true because it is very important to him that he meet new people at college. If Erik uses the scientific method to investigate this, what type of research would he be doing? multiply (3x^2-2x)(2x^2+3x-1) Compared with its corresponding unsaturated fatty acid, a saturated fatty acid has _____. more hydrogen less hydrogen more oxygen less oxygen Which expressions can be used to find m angle ABC? Selecttwo options. What is the solution to 2x^2+8x=x2-16? x=4, x=-2, x=2, x=4 when did the feudalism begin? In Europe, approximately 4% of people are red-haired, mostly due to a recessive mutation in the melanocortin 1 receptor (MC1R). If the population is in Hardy-Weinberg equilibrium, what is the likelihood that a non-redheaded European is a carrier for the MC1Rr allele? (For the purpose of this problem, assume all redheads and carriers are mutant for the same MC1R allele). A: 22%B: 33% C: 11%D: 44% Identify each line or segment that intersects S. A star has a mass of 1.48 x 1030 kg and is moving in a circular orbit about the center of its galaxy. The radius of the orbit is 1.9 x 104 light-years (1 light-year = 9.5 x 1015 m), and the angular speed of the star is 1.8 x 10-15 rad/s. (a) Determine the tangential speed of the star. (b) What is the magnitude of the net force that acts on the star to keep it moving around the center of the galaxy? Which of these could be a good reason to end a dating relationship? A.Your partner wants to do things with friends B.Your partner practices active listening with you C. Your partner exhibits controlling behaviors D.Your partner apoligizes when there is a disagrement The man was charged with obstruction of justice. In myopinion, the man was unfairly accused. His trial will last forthree days.Which phrase from this passage is a subjective element that makes thepassage less trustworthy?OA. His trial will last for three daysOB. In my opinionDC. The man was chargedD. Obstruction of justice A rectangular solid object is 3 in. high, 6 in. long and 2 in. wide. What is its volume? Please provide a definition of an unconditioned reflex. A candy company that makes colored candies claims that 10% of the candies it produces are green and that bags are packed randomly. In a really large bag of candies, we found 12% of 500 candies were green. Is this evidence that the manufacturing process is out of control and has made too many greens? Explain. Simplify square root of 300x8/ 27x12